Distribution of the 21-gene breast recurrence score in patients with primary breast cancer in Germany = Verteilung des 21-Gen-Rezidiv-Scores bei Patientinnen mit primärem Mammakarzinom in Deutschland - Walter, Vincent P.; Wallwiener, Markus (Geburtshilfe und Frauenheilkunde, 2020)
Multigene assays are being used increasingly to aid in decision-making about chemotherapy in breast cancer. Here, we present the 21-gene recurrence score (RS) of patients tested in routine clinical practice in Germany. Patients and Methods In a retrospective analysis, 4695 patients with hormone receptor-positive and HER2-negative early breast cancer (pT1 - 3, pN0 - 1, M0) were included in whom RS testing was conducted in Germany between November 2015 and July 2018. RS groups as defined in the TAILORx trial (RS result 0 - 10; 11 - 25; 26 - 100) were used. Results Of these patients, 21% were assigned to the low RS group, 63% to the midrange RS group, and 15% to the high RS group. 1772 (81%) of 2175 node-negative patients over 50 years of age were grouped either into the low RS group or the midrange RS group. The portion of patients with a low or midrange RS was 90% among node-positive patients (1284 of 1432 patients), 79% among patients with Ki-67-high (≥ 20%) tumors (1829 of 2310 patients), 86% vs. 70% among patients with G2 and G3 tumors (3244 of 3762 patients and 368 of 522 patients), respectively, 88% among patients with a tumor size of > 5 cm (140 of 159 patients), and 82% among node-negative patients at high clinical risk (1110 of 1352). Conclusions The distribution of the 21-gene RS in German patients that were tested in routine clinical practice indicates that, according to the results of the TAILORx trial, chemotherapy may not be beneficial in most of these.
Gesehen am 15.12.2021